تطور القضاء الدستوري في الجزائر - بشرة قندوز; معمر عوادي (My University, 2022)
Summary: Algeria has always endeavoured through its legal system to embody the rule of law and to enshrine the principle of the supremacy of the Constitution and to guarantee and protect the rights and freedoms of individuals. The constitutional judiciary, as a guarantee of achieving all the above, has undergone several developments from independence to the present day, However, the constitutional amendment of 2020 served as the key milestone in Algeria's constitutional oversight. Particularly since the constitutional amendment of 2016 paved the way for this change by introducing the mechanism for the exception of unconstitutionality as a judicial means for the exercise of constitutional justice, The constitutional founder should only in keeping with this trend by adopting judicial oversight through the Constitutional Court and abandoning the political censorship exercised by the Constitutional Council, which proved its shortcomings. The Algerian constitutional founder has thus succeeded in establishing constitutional justice in his legal arsenal smoothly and literally. ............................... الملخص لطالما سعت الجزائر من خلال منظومتها القانونية إلى تجسيد دولة القانون وتكريس مبدأ الدستور وضمان حقوق وحريات الأفراد وحمايتها، وقد مر القضاء الدستوري كضمانة لتحقيق كل ما سبق بعدة تطورات منذ الاستقلال إلى يومنا هذا، إلا أن التعديل الدستوري لعام 2020 كان بمثابة المنعرج الأساسي في مجال الرقابة الدستورية في الجزائر، لاسيما وأن التعديل الدستوري لعام 2016 كان قد مهد لهذا التغيير من خلال استحداثه لآلية الدفع بعدم الدستورية كوسيلة قضائية لممارسة العدالة الدستورية فما كان على المؤسس الدستوري إلا أن يساير هذا التوجه من خلال تبنيه للرقابة القضائية عن طريق المحكمة الدستورية وتخليه عن الرقابة السياسية التي كان يمارسها المجلس الدستوري والتي أثبتت قصرها وبذلك يكون المؤسس الدستوري الجزائري قد نجح في إرساء معالم العدالة الدستورية ضمن ترسانته القانونية بكل سلاسة وحرفية. ....................... Résumé : L’Algérie s’est toujours efforcée, par son système juridique, d’incarner l’État de droit et de consacrer le principe de la suprématie de la Constitution et de garantir et de protéger les droits et libertés des individus. Le pouvoir judiciaire constitutionnel, comme une garantie de réaliser tout ce qui précède, a subi plusieurs développements de l’indépendance à nos jours, Cependant, l’amendement constitutionnel de 2020 a servi de jalon clé dans le contrôle constitutionnel de l’Algérie. D’autant que l’amendement constitutionnel de 2016 a ouvert la voie à ce changement en introduisant le mécanisme d’exception à l’inconstitutionnalité comme moyen judiciaire pour l’exercice de la justice constitutionnelle, Le fondateur constitutionnel ne devrait suivre cette tendance qu’en adoptant le contrôle judiciaire par le biais de la Cour constitutionnelle et en abandonnant la censure politique exercée par le Conseil constitutionnel, qui a prouvé ses lacunes. Le fondateur constitutionnel algérien a ainsi réussi à établir la justice constitutionnelle dans son arsenal juridique sans heurts et littéralement.